PRAK Promotes the Pathogen Clearance by Macrophage Through Regulating Autophagy and Inflammasome Activation - Mi, Ligu; Wang, Yan; Xu, Hui; Wang, Yu; Wu, Jia; Dai, Hui; Zhang, Yu (Frontiers in Immunology, 2021)
The p38 regulated/activated protein kinase (PRAK) is a protein kinase downstream of p38MAPK. The present study investigated its function in the macrophage. Myeloid-specific deletion of Prak resulted in a significant reduction in F4/80+CD11b+ peritoneal macrophages with decreased expression of MHC-II and CD80. Upon infection with Listeria monocytogenes, Prak-deficient mice demonstrated an increased mortality, which was accompanied by a higher bacterial load in multiple tissues and elevated levels of proinflammatory cytokines in the serum. While the Prak-deficient macrophage showed similar potency in phagocytosis assays, its bactericidal activity was severely impaired. Moreover, Prak deficiency was associated with defects in ROS production, inflammasome activation as well as autophagy induction. Therefore, PRAK critically contributes to the clearance of intracellular pathogens by affecting multiple aspects of the macrophage function.